Successful restoration of moth abundance and species-richness in grassland created under agri-environment schemes. (September 2017) - Alison, Jamie; Duffield, Simon J.; Morecroft, Michael D.; Marrs, Rob H.; Hodgson, Jenny A.
Abstract: Restoring intensive agricultural fields to species-rich semi-natural grassland could have profound effects on biodiversity and ecosystem services. However, only a minority of European agri-environment scheme funding is currently devoted to such measures (< 1% in the UK) and too few studies compare biodiversity on restored habitats with that on appropriate control and reference sites. As a result, there is a lack of advice for land managers on how to implement habitat restoration to maximise conservation outcomes, especially for insects. We present a landscape-scale field study in which we tested whether the abundance and species-occurrence of moths (Lepidoptera) differed between arable fields, fields restored to species-rich grassland, and semi-natural calcareous grassland (CG). We also tested whether moths were affected by the frequency of CG indicator wildflowers, age of restoration and habitat connectivity of restored grassland. We found that the abundance of CG-associated moths on restored grassland was almost eight times that on arable fields, and abundance and species-occurrence did not differ significantly from that on semi-natural CG. The only group of moths that was more abundant on CG than restored grassland was associated with late successional stage habitats (e.g. woodland), which shows that trees and shrubs are key features maintaining insect biodiversity on CG. CG moths were more abundant on restored grassland sites where CG indicator wildflowers had established, suggesting that active enhancement of the plant community can increase the abundance of target insect groups. Restoring arable fields to species-rich grassland benefits moths over short timescales (as little as 3 years) and at great distances from semi-natural CG (up to 7 km). It should play a pivotal role in future agri-environment schemes aiming to increase insect biodiversity.